Pharmacological Properties of Synthetic Cannabinoids, Specifics of Their Detection and Forensic Examination - Serdega, O. M. (Вісник Харківського національного університету внутрішніх справ, 2025)
The illegal circulation of synthetic cannabinoids intensifies criminal threats and negatively impacts vulnerable segments of the population due to their specific effects on the human psychophysiological state. This article examines the historical background of the recreational use of synthetic cannabinoids and their emergence in the illicit drug market. It presents data from contemporary neurobiological studies dedicated to these compounds. The article analyzes both the therapeutic potential of synthetic cannabinoids and the adverse effects of their misuse in uncontrolled settings. It identifies key issues that must be addressed to resolve challenges in the forensic examination of objects containing these psychotropic substances and outlines the specific features of their detection and seizure. Recommendations are provided for forensic experts in the field of narcotic drugs and psychotropic substances regarding the selection of chemical analysis methods for solutions or herbal mixtures that may contain synthetic cannabinoids. The article evaluates the applicability of instrumental analysis techniques for the qualitative identification and quantitative determination of target compounds, especially in the presence of masking agents or interfering processes during sample preparation and analysis. Based on the study, both the positive and negative aspects of synthetic cannabinoid use are outlined, along with the most effective methods for their examination in laboratory and field conditions. The article also highlights prospects for further research into the long-term effects of synthetic cannabinoids on human physiological and mental health, their neurotoxicity, and mutagenic potential. Overall, the findings contribute to the integration of pharmacological and forensic research data into practical application.